Two penzigioid Xylaria species described from China based on morphological and molecular characters - Ma, Hai-Xia; Qu, Zhi; Peng, Mingkai; Li, Yu (Phytotaxa, 2020)
A new pyrenomycetous fungus, Xylaria acericola, collected in Jilin Province, northeastern China, is described and illustrated on the basis of two collections. Both morphology and phylogenetic analysis of rDNA ITS and β-tubulin sequences support the establishment of this new species. Macroscopically, the new species is characterized by penzigioid stromata erumpent through bark of host plant. Microscopically, it has dark-brown to black, ellipsoid-inequilateral ascospores and large, urn-shaped ascus apical ring bluing in Melzer’s reagent. The differences between the new species and the related fungi are discussed. Another penzigioid Xylaria species, X. sibirica, is reported in China for the first time.